HISTORY OF CARBONATE ION CONCENTRATION OVER THE LAST 100 MILLION YEARS - Tyrrell T.; Zeebe R.E. (My University, 2004)
Instead of having been more or less constant, as once assumed, it is now apparent that the major ion chemistry of the oceans has varied substantially over time. For instance, independent lines of evidence suggest that calcium concentration ([Ca2+]) has approximately halved and magnesium concentration ([Mg2+]) approximately doubled over the last 100 million years. On the other hand, the calcite compensation depth, and hence the CaCO3 saturation, has varied little over the last 100 My as documented in deep sea sediments. We combine these pieces of evidence to develop a proxy for seawater carbonate ion concentration ([CO32?]) over this period of time. From the calcite saturation state (which is proportional to the product of [Ca2+] times [CO32?], but also affected by [Mg2+]), we can calculate seawater [CO32?]. Our results show that [CO32?] has nearly quadrupled since the Cretaceous. Furthermore, by combining our [CO32?] proxy with other carbonate system proxies, we provide calculations of the entire seawater carbonate system and atmospheric CO2. Based on this, reconstructed atmospheric CO2 is relatively low in the Miocene but high in the Eocene. Finally, we make a strong case that seawater pH has increased over the last 100 My.